Implementation of Prenatal Children's Education in an Islamic Perspective (Implementasi Pendidikan Anak Prenatal dalam Perspektif Islam) - Izmi Nopianda; Umi Hijriyah; Heny Wulandari (Institut Agama Islam Negeri (IAIN) Kendari, 2022)
This article aims to analyze the implementation of prenatal education for children in an Islamic perspective and what factors influence the implementation of prenatal education for children in Pekon Sukamara, Bulok District, Tanggamus Regency. The research was conducted qualitatively with a descriptive approach, where data was collected through observation, interviews and documentation studies. The analysis was carried out in three stages, namely data reduction, data presentation and verification. The results of the study show that parents (pregnant women and their families) have implemented what prenatal education is and have done it through several methods including song methods, prayer methods, prayer methods, kinesthetic methods, storytelling/communication methods, listening to recitation methods at the taklim assembly, audio method, dhikr method, relaxation method. Then the factors that encourage and inhibit the process of educating a child in the womb are economic factors, educational factors, environmental factors, family conditions, emotional factors and support from the people around them.Keywords: Prenatal Education, Islam